1996
DOI: 10.1021/jf960113v
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Actomyosin and Expressible Moisture of Frozen Stored Striated Adductor Muscles of Aulacomya ater ater (Molina):  Effects of Polyphosphates

Abstract: Aulacomya adductor muscles with and without prior immersion in polyphosphates were frozen and stored at −30 °C. Expressible moisture of control samples increased after freezing and showed the highest increment at the second week of storage. Actomyosin extractability was not affected by freezing but decreased during frozen storage in both untreated and treated muscles. The reduced viscosity and the Mg2+-ATPase activity of actomyosin in dip-treatment free muscles fell with freezing and frozen storage. Polyphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…We reported in a previous work that a thick filament of the marine invertebrate Aulacomya ater ater (Molina) aggregates faster than a thin filament during frozen storage of striated adductor muscles (Paredi et al, 1996). The present work showed that the thick filament of squid mantle was also affected by frozen storage.…”
Section: Resultssupporting
confidence: 61%
“…We reported in a previous work that a thick filament of the marine invertebrate Aulacomya ater ater (Molina) aggregates faster than a thin filament during frozen storage of striated adductor muscles (Paredi et al, 1996). The present work showed that the thick filament of squid mantle was also affected by frozen storage.…”
Section: Resultssupporting
confidence: 61%
“…The myofibrillar ATPases have been widely used as a measure of actomyosin integrity (Roura, Montecchia, Goldemberg, Trucco, & Crupkin, 1990;Paredi, De Vido De Mattio, & Crupkin, 1996;Benjakul, Seymour, Morrisey, & An, 1997). The activity of the Ca 2+ -dependent Mg 2+ ATPase is a characteristic activity of invertebrate actomyosin (Konno, Arai, Yoshida, & Watanabe, 1981;Paredi et al, 1990).…”
Section: Enzymatic Activity and Protein Surface Hydrophobicitymentioning
confidence: 99%
“…There are mainly physicochemical changes of proteins and lipids, as well as changes in shelf life and general sensory quality 3, 4. The influence of freezing on fish muscle proteins has been described in many publications and it mainly concerns the changes in solubility of protein fractions,5–10 their water‐holding capacity,11, 12 the activity of proteolytic enzymes,13–16 and the influence of these changes on meat texture and sensory quality 17. The hydrolytic and oxidative changes of fish lipids during freezing are mainly related to the high concentration of polyunsaturated fatty acids18, 19 and the concentration of pro‐oxidative solutions 20…”
Section: Introductionmentioning
confidence: 99%